2018
DOI: 10.1016/j.foodres.2018.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity of artisanal cheese from the Amazonian region of Brazil during the dry and rainy seasons

Abstract: The microbiota from artisanal cheeses produced in the Amazonian region is evaluated. Samples of artisanal cheeses were obtained from markets in Conceição do Araguaia and Redenção (Pará, Brazil) over rainy and dry seasons, and their biodiversity was assessed by culture-dependent and culture-independent methods. Mean counts of lactic acid bacteria (LAB) in cheeses ranged from 7.32 to 8.84 log CFU/g, for both seasons. Members of genera Lactobacillus, Lactococcus, Weissella, Enterococcus, Pediococcus, and Leuconos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 50 publications
0
15
0
2
Order By: Relevance
“…On the other hand, the main effect on the cheese surface was on M. caseolyticus. M. caseolyticus (family Staphylococcaceae) usually originates from animal organs, the farm environment, milk, and cheese (25)(26)(27)(28). M. caseolyticus was previously found on the surfaces of Italian cheeses, such as taleggio, gorgonzola, casera, scimudin, and formaggio di fossa (29), and it is probably able to break down caseins, contributing to the formation of aroma precur-sors (30).…”
mentioning
confidence: 99%
“…On the other hand, the main effect on the cheese surface was on M. caseolyticus. M. caseolyticus (family Staphylococcaceae) usually originates from animal organs, the farm environment, milk, and cheese (25)(26)(27)(28). M. caseolyticus was previously found on the surfaces of Italian cheeses, such as taleggio, gorgonzola, casera, scimudin, and formaggio di fossa (29), and it is probably able to break down caseins, contributing to the formation of aroma precur-sors (30).…”
mentioning
confidence: 99%
“…Several authors (Bemfeito et al, 2016;Martins et al, 2018;Nóbrega, 2012;Rodrigues et al, 2019) reported sensory changes in cheese over the consumption/maturation as related in the diaries.…”
Section: Cheese Sensory Profile Over Consumptionmentioning
confidence: 99%
“…Lactococcus lactis ssp. lactis, isolated from artisanal cheese (Martins et al, 2018), was selected because of its known thermosensitivity. An aliquot of 100 µL of the strain was transferred to 10 mL of de Man, Rogosa, and Sharpe broth (MRS, Difco, Bordeaux, France) and incubated at 30°C for 18 h. An aliquot of 2.5 mL of this pre-activated culture was inoculated into 250 mL of MRS broth and incubated at 30°C for 18 h. The cell suspension was centrifuged (5,000 × g for 10 min at 25°C; Eppendorf, Hamburg, Germany) and the pellet (cell concentrate) was washed twice in saline solution 0.85% (wt/vol).…”
Section: Short Communicationmentioning
confidence: 99%